South Africa Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2016)
The main purpose of the South Africa Report on the Observance of Standards and Codes, Accounting and Auditing (ROSC A&A) is to determine reforms that will continue to improve the quality of financial reporting in South Africa. The review, requested by the Minister of Finance, was conducted to assess the status of implementation of policy recommendations in the prior 2003 ROSC A&A report, assess the institutional framework underpinning accounting and auditing practices in comparison with international standards and good practices in order to identify any emerging issues that require strengthening, share good practices adopted in the country, and propose policy recommendations addressing areas that require improvements. Implementation of the policy recommendations will further enhance the quality of financial reporting in the country, a key pillar that contributes to enhancing the business environment and advancement of governance and financial accountability in both the private and public sector entities. The review focuses on private sector. Financial reporting in public sector is assessed under public expenditure and financial accountability framework.